[Monday Club interior] - The Monday Club::::::photographer::: (1940)
Interior photograph of the Monday Club's stage. Based on the updated light fixtures, this photograph was probably taken in the 1940s-1950s. This photograph was previously stored in Box 2 in a series titled Photos and News Clippings, 1934.